Diet quality among pregnant women in the Navajo Birth Cohort Study. Issue 3 (5th February 2020) - De La Rosa, Vanessa Y.; Hoover, Joseph; Du, Ruofei; Jimenez, Elizabeth Yakes; MacKenzie, Debra; Lewis, Johnnye
Abstract: Proper nutrition during pregnancy is vital to maternal health and fetal development and may be challenging for Navajo Nation residents because access to affordable and healthy foods is limited. It has been several decades since reported diet quality during pregnancy was examined on Navajo Nation. We present the first study to estimate iodine intake and use the Healthy Eating Index (HEI‐2015) to assess maternal diet quality among pregnant women in the Navajo Birth Cohort Study (NBCS). Based on dietary intake data derived from food frequency questionnaires, overall estimated micronutrient intake has remained similar since the last assessment in 1981, with potential improvements evident for folate and niacin. A high proportion of women (>50%) had micronutrient intakes from dietary sources below the Estimated Average Requirements during pregnancy. The median urinary iodine concentration for NBCS women (90.8 μg/L; 95% CI [80, 103.5]) was less than adequate and lower than concentrations reported for pregnant women that participated in the National Health and Nutrition Examination Survey (NHANES) between 2011 and 2014. Overall, average diet quality of NBCS women estimated using the HEI‐2015 (62.4; 95% CI [60.7, 64.0]) was similar to that reported for women of child‐bearing age and pregnant women in NHANES. Although, NBCS women had diets high in added sugar, with sugar‐sweetened beverages as the primary contributors. Our study provides updated insights on maternal diet quality that can inform health and nutrition initiatives in Navajo communities emphasizing nutrition education and access to prenatal vitamins and calcium, iodine, and vitamin E dense foods.